Cycloartane triterpenoid as an insulin mimicking agent - Darnis, Deny Susanti; Mohamed Amiroudine, Mohamed Zaffar Ali; Bakhtiar, M. Taher; Ichwan, Solachuddin J. A.; Kaderi, Mohd Arifin (2012)
The incidence of type 2 diabetes and the resultant metabolic syndrome are rapidly increasing. In this study, we investigated the effects of cycloartane triterpenoids on the adipocyte differentiation and glucose uptake in 3T3-L1 adipocytes together with its mechanism. The cells were treated for lipid accumulation with different concentration of cycloartane by using Oil Red O staining. After day-8 of treatment, morphological changes and high lipid accumulation effects were observed in these cells (p<0.05). In addition, the intracellular fat accumulation increased by 1.9 fold relative to MDI-treated control cells at concentration of 50 µM. The insulin-induced 2-deoxy-D-[3H] glucose uptake also was significantly increased (p<0.01) in cycloartane treated cells as compared to the basal. Moreover, the adipocytes differentiated by cycloartane exhibited insulin sensitivity as demonstrated by a significant increase in glucose uptake. Further evaluation of the mechanism of related gene expression by using the quantitative RT-PCR shows that mature adipocytes treated with cycloartane increased the expression levels of PPARγ which regulate the adipogenesis process and its target gene GLUT4 that involve in glucose uptake. In conclusion, these findings suggest that cycloartane triterpenoids from adipocyte differentiation and glucose uptake by stimulation of PPARγ and GLUT4 expression.